Une nouvelle méthode pour estimer l’âge au décès des adultes à partir de la surface sacro-pelvienne iliaque - Aurore Schmitt (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Many studies have shown that the method proposed by Lovejoy et al. (1985) to assess adult age at death from the sacro-pelvic surface of the ilium is not reliable. After a detailed study of the variability of this indicator with age on several osteological samples, we developed a methodology which takes into account this parameter and avoids the current methodological biases. These studies result in a new method elaborated from several European populations, based on a simple notation system and on the calculation of probabilities enabling attribution to an age category.